Phylogenetic relationships and divergence times of Odonata inferred from mitochondrial genome - Weidong Huang; Tianyou Zhao; Mingyuan Fan; Yuange Duan; Li Tian; Hu Li; Wanzhi Cai; Fan Song (iScience)
Summary: Understanding the origin and evolutionary history of Odonata are crucial, as they represent central members of the first winged lineages. Here, we assembled the largest mitogenome dataset to date, comprising 143 mitogenomes representing three suborders, 18 families, of which 53 mitogenomes were newly sequenced. Phylogenetic inferences demonstrate that the mitogenome is a powerful tool for resolving lower-level divergence within Odonata, and it falls short in addressing higher-level relationships like suborder, superfamily, and interfamily classifications. The evolutionary history of Odonata was reconstructed by incorporating 11 fossil records, estimating the origin of Odonata occurred in the Jurassic, with the Cretaceous emerging as a critical period for the initial radiation of main Odonata lineages. Furthermore, we employed fossil calibration strategies from various studies to calibrate our analyses, enabling the investigation of mito-nuclear discordance patterns in divergence time inferences. Our results revealed significant differences in divergence time estimates inferred solely from mitochondrial or nuclear data within Odonata, particularly pronounced when using older upper bounds values for fossils.